2015
DOI: 10.1111/hir.12102
|View full text |Cite
|
Sign up to set email alerts
|

Parents of children with disabilities in Kuwait: a study of their information seeking behaviour

Abstract: Information sources and services for Kuwaiti parents of disabled children need further development and improvement. Librarians and other information professionals can assist by providing parents with information appropriate to their stage in understanding the child's diagnosis and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 19 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Within the context of information behaviour following during and after diagnosis, Al‐Dahani et al . used nonparametric tests to analyse the results of 240 questionnaires of participants at a school for children with special need.…”
Section: In This Issue…mentioning
confidence: 88%
See 1 more Smart Citation
“…Within the context of information behaviour following during and after diagnosis, Al‐Dahani et al . used nonparametric tests to analyse the results of 240 questionnaires of participants at a school for children with special need.…”
Section: In This Issue…mentioning
confidence: 88%
“…Within the context of information behaviour following during and after diagnosis, Al-Dahani et al 2 used nonparametric tests to analyse the results of 240 questionnaires of participants at a school for children with special need. Al-Dahani et al examined information seeking behaviour investigating both information source preference and barriers encountered in seeking information.…”
Section: Referencesmentioning
confidence: 99%
“…They found 7 Occupational Therapy International that information regarding problems associated with ADHD, behavioural management, social skills, and educational strategies was considered important by almost every family (93-99%). With respect to the Kuwaiti population, Al-Daihani and Al-Ateeqi [44] surveyed 240 parents of children with special needs and found that a lack of information to help parents cope with their child's problem was the second highest barrier for the parents, after a lack of resources in Arabic.…”
Section: Limited Understanding Of the Value Of Playmentioning
confidence: 99%
“…The information resources and facilities of the academic library that devoted to the BVI students in the Arab countries have received recently much research attention (Hada, 2014; Al-Daihani and Al-Ateeqi, 2015; Abdelrahman, 2016; Al-Harrasi, 2016; Salih and Kakizawa, 2016). These research studies investigated the efforts of the academic libraries in introducing information services dedicated to BVI students.…”
Section: Literature Reviewmentioning
confidence: 99%